Study of Tribological Behavior for Chromium Based Coatings Deposited on Conventional Materials. (2016) - Dave, Divyesh P.; Chauhan, Kamlesh V.; Chavda, Mahesh R.; Rawal, Sushant K.
Abstract: This paper reports on tribological behavior of chromium based coating deposited by RF reactive magnetron sputtering process. The study is conducted on conventional tooling materials such as aluminum, brass and mild steel that were used as substrates. The tribological properties of uncoated pins of aluminum, brass and mild steel with same diameters and after applying chromium based coatings were measured by pin on disc tribometer. Conventional materials are subjected to high cyclic loading, friction, wear and fatigue resulting in high levels of abrasion. It was observed that application of chromium based coating prolongs the reliability and service lifespan of these conventional materials by enhancing their wear resistance.